(untitled) (Journal of Faculty of Education, 2021)
Disabled girls effective participation in the invironomental activities is of great importance .This assures the importance of disabled girls participation in the physical activities spcially those whose mentally disabled.The studies and researches support the professtional and those who work in the field of physical education and direct them towards the dialy practice of sports and the advantages of physical activity for its benefit for human brain soul and body. The study aimed at revealing the relation- ship between physical activities and the health benefits for their practice.For the purpose of the study questionaires were used, directed to disabled girls parents (the mental age 2-16 years) in order to identify the relation-ship between physical activity and its influence on the different aspects of growth .The finding showed that the parents in the Kingdom of Saudi Arabia have positive attitudes.